2019
DOI: 10.1111/1750-3841.14747
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Function of Buckwheat‐Resistant Starch Supplementation on Lipid Profile and Gut Microbiota in Mice Fed with a High‐Fat Diet

Abstract: Buckwheat‐resistant starch (BRS) has shown to be a nutrient capable of lowering cholesterol and reducing obesity. In this study, the regulatory effects of tartary buckwheat starch on blood lipid level and gut microbiota (Lactobacillus, Bifidobacterium, Enterococcus, and Escherichia coli) in mice fed with a high‐fat diet was investigated. Male C57BL/6 mice were separately fed with a normal diet (CON), a high‐fat diet (HFD), and high‐fat diet supplemented with buckwheat‐resistant starch (HFD+BRS) for 6 weeks. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 33 publications
2
28
0
3
Order By: Relevance
“…We demonstrated that antibiotic use during pregnancy, cesarean section, high-fat, low-carbohydrate diets, antibiotic use in the past year, and alcohol consumption are independent risk factors for CSU. Recent evidence revealed that a high-fat diet in mice altered the intestinal microbiota composition; specifically, the number of Bifidobacterium were significantly reduced (Zhou et al, 2019). Several studies have shown that the administration of antibiotics can lead to disorders of intestinal flora and decreased microbial diversity (Angelucci et al, 2019;Sun et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that antibiotic use during pregnancy, cesarean section, high-fat, low-carbohydrate diets, antibiotic use in the past year, and alcohol consumption are independent risk factors for CSU. Recent evidence revealed that a high-fat diet in mice altered the intestinal microbiota composition; specifically, the number of Bifidobacterium were significantly reduced (Zhou et al, 2019). Several studies have shown that the administration of antibiotics can lead to disorders of intestinal flora and decreased microbial diversity (Angelucci et al, 2019;Sun et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…To provide health benefits, current dietary guidelines suggest that starchy foods should contain at least 14% of RS on a total starch basis (EFSA, 2011). Among pseudocereals, common and tartary buckwheat have the highest levels of resistant starch (27-33.5%) (Skrabanja et al, 1998;Zhou et al, 2019a).…”
Section: Carbohydratesmentioning
confidence: 99%
“…The high levels of RS observed in buckwheat were proven: 1) to modulate blood glucose and lipid levels, 2) to regulate intestinal microbiota, and 3) to reduce obesity (Zhou et al, 2019a).…”
Section: Carbohydratesmentioning
confidence: 99%
“…The major nutritional components in buckwheat seeds are represented by the carbohydrates that vary between 63.1 and 82.1%, of which from 54.5% to 54.7% was found to be starch [9] with a relatively high level of amylose (18.3%-47% of total starch) [10]. Moreover, buckwheat has high levels of resistant starch (27%-33.5%) which provides health benefits [11]. Buckwheat starch is concentrated in the endosperm, similarly to common cereals, while protein and lipids are located in the embryo that extends through the starchy endosperm [12].…”
Section: Introductionmentioning
confidence: 99%
“…Buckwheat grains represent an excellent source of dietary fiber (17.8%) with a low ratio of soluble-insoluble dietary fiber (0.5-0.28) [13]. The protein content of buckwheat ranges from 5.7% to 14.2%, depending on the variety and environmental conditions [11]. Buckwheat protein is characterized by a high biological value due to its excellent amino acids balance [14] and it is close to the optimum composition suggested by FAO/WHO [15], making buckwheat an essential contributor to human protein intake.…”
Section: Introductionmentioning
confidence: 99%